Antibody drug conjugates with hydroxamic acid cargos for histone deacetylase (HDAC) inhibition. Issue 7 (12th January 2021) - Cianferotti, Claudio; Faltoni, Valentina; Cini, Elena; Ermini, Elena; Migliorini, Francesca; Petricci, Elena; Taddei, Maurizio; Salvini, Laura; Battistuzzi, Gianfranco; Milazzo, Ferdinando Maria; Anastasi, Anna Maria; Chiapparino, Caterina; et al.
Abstract : The bioconjugation of hydroxamic acids to antibodies has been made possible through a non-cleavable linker based on the p -mercaptobenzyl alcohol structure that releases hydroxamates in the cells. Abstract : Antitumor hydroxamates SAHA and Dacinostat have been linked to cetuximab and trastuzumab through a non-cleavable linker based on the p -mercaptobenzyl alcohol structure. These antibody drug conjugates (ADCs) were able to inhibit HDAC in several tumour cell lines. The cetuximab based ADCs block human lung adenocarcinoma cell proliferation, demonstrating that bioconjugation with antibodies is a suitable approach for targeted therapy based on hydroxamic acid-containing drugs. This work also shows that ADC-based delivery might be used to overcome the classical pharmacokinetic problems of hydroxamic acids.